Knowing to Preserve: Vaulted Maya Architecture - Gilabert Sansalvador, Laura (Restauro Compás y Canto S.A., 2021)
The study of Maya architecture has traditionally been approached from the discipline of archaeology. The constructive and structural studies of the buildings, as well as the analysis of the degradation processes that affect them, have had less importance. However, this internationally recognized cultural heritage presents complex conservation situations that require the collaboration of multidisciplinary teams. The work presented here is part of a recent research on the Maya vault, the most advanced roofing system of this architecture and perhaps one of the best expressions of this civilization’s technological evolution. Based on an exhaustive collection of field data, with special emphasis on the constructive aspects, the main pathological agents and degradation mechanisms affecting Maya vaulted buildings were analyzed. This made it possible to verify that the constructive features of these buildings, as well as their construction process, determine in many cases not only their stylistic features, but also their forms of collapse. This paper shows the incidence of the constructive aspects of the Maya vaulted buildings in their process of deterioration and collapse.